1998
DOI: 10.1128/jcm.36.1.273-274.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Screening and Commercial Methods for Detection of Methicillin Resistance in Coagulase-Negative Staphylococci

Abstract: The National Committee for Clinical Laboratory Standards recommends 48 h of incubation by the oxacillin salt agar screen (OSAS) method for the detection of methicillin-resistant coagulase-negative staphylococci (CoNS). An earlier identification of methicillin resistance is desirable. The time to detection of the mecAgene by PCR was compared with the times to detection by OSAS, by the oxacillin disk diffusion (ODD) method, and with MicroScan Gram Positive Combo type 6 panels (MicroScan Inc. Sacramento, Calif.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…Even though researchers have shown that an agar screening test containing 6 ìg oxacillin ml À1 is not efficient towards CNS (Tenover et al, 1999), and it is no longer recommended for CNS (NCCLS, 1999), comparative studies to assess the agar screening test and disc-diffusion have pointed out that agar screening is more sensitive for identifying methicillinresistant strains (York et al, 1996;Hussain et al, 1998;Frebourg et al, 1998;Kohner et al, 1999). For the agar screening test we used Mueller-Hinton agar plates supplemented with 4 % NaCl and incubated for 48 h because, under these conditions, methicillin resistance coded by the mecA gene is easily characterized (York et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Even though researchers have shown that an agar screening test containing 6 ìg oxacillin ml À1 is not efficient towards CNS (Tenover et al, 1999), and it is no longer recommended for CNS (NCCLS, 1999), comparative studies to assess the agar screening test and disc-diffusion have pointed out that agar screening is more sensitive for identifying methicillinresistant strains (York et al, 1996;Hussain et al, 1998;Frebourg et al, 1998;Kohner et al, 1999). For the agar screening test we used Mueller-Hinton agar plates supplemented with 4 % NaCl and incubated for 48 h because, under these conditions, methicillin resistance coded by the mecA gene is easily characterized (York et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) to detect the mecA gene as a rapid method for the identification of MRSA has been amply demonstrated (11,(20)(21)(22)(23)(24)(25)(26)(27). Some even consider PCR to be the method of choice for identifying MRSA and other methicillinresistant staphylococci (8,(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…In order to encourage appropriate use of β lactam antibiotics for CNS infections, several approaches have been proposed to improve in vitro susceptibility testing performance. [5][6][7][8][9] These techniques aim to show heteroresistance by phenotyping or finding resistance genes by molecular techniques. In this report, we illustrate the application of one such technique to the successful treatment of six patients with invasive CNS infections.…”
mentioning
confidence: 99%